Ecological response of two hydro‐morphological similar pre‐dams to contrasting land‐use in the Rappbode reservoir system (Germany). Issue 5 (October 2014) - Friese, Kurt; Schultze, Martin; Boehrer, Bertram; Büttner, Olaf; Herzsprung, Peter; Koschorreck, Matthias; Kuehn, Burkhard; Rönicke, Helmut; Tittel, Jörg; Wendt‐Potthoff, Katrin; Wollschläger, Ute; Dietze, Maren; et al.
<x xml:space="preserve">Abstract</x> Two morphologically similar pre‐dams (Hassel and Rappbode pre‐dams, Harz Mountains, Germany) of a large reservoir with different land use in their catchments were compared with respect to their physical, chemical, and biological properties in order to test if differences can be attributed to the different land use. In addition, local geology, soil types, and topography were evaluated in detail to distinguish its influence from that of present‐day land use. Despite a remarkable similarity in physical variables and stratification, the annual development of hydrochemistry and biology differed between Rappbode and Hassel pre‐dam. While the Hassel pre‐dam received much higher nitrogen and phosphorus inputs from the catchment, the Rappbode pre‐dam received more dissolved organic carbon. The quality of dissolved organic carbon also differed between the two catchments, indicating different sources. The higher residence time of Hassel pre‐dam amplified the effects of these inputs on the trophic state of both pre‐dams. The phytoplankton communities in summer were dominated by diatoms in the Rappbode pre‐dam and by cyanobacteria in the Hassel pre‐dam. In conclusion, land use appeared to be an important driver for the observed lake characteristics. However, it was itself strongly related to soil types and topography, which on the other hand influences the residence time of water within the catchments.